Research Productivity of International Branch Campuses - Lane, Jason; Pohl, Hans (International Higher Education, 2020)
Using scientometric data, this article explores the research productivity of international branch campuses. The data reveals that one-third of IBCs engage in at least minimum levels of research productivity, with the most productive exceeding 400 publications annually. While research production is minimal across the majority of IBCs, the data evidences how some IBCs are significant contributors to the internationalization of research and to the overall research productivity of their host nations.